2018
DOI: 10.1093/ajh/hpy083
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Induced Morphological and Physiological Changes in Cells of the Arterial Wall

Abstract: Morphological and physiological changes in the vasculature have been described in the evolution and maintenance of hypertension. Hypertension-induced vascular dysfunction may present itself as a contributing, or consequential factor, to vascular remodeling caused by chronically elevated systemic arterial blood pressure. Changes in all vessel layers, from the endothelium to the perivascular adipose tissue (PVAT), have been described. This mini-review focuses on the current knowledge of the structure and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 130 publications
0
46
0
9
Order By: Relevance
“…Vascular smooth muscle cell structural changes in cardiovascular diseases and aging are collectively termed vascular remodeling [40]. Vascular remodeling is observed when there is a change in diameter of a fully relaxed vessel that is not explained by a change in transmural pressure or compliance, and thus is structural in nature [40]. Remodeling can be increase (hypertrophic), no change (eutrophic) or decrease (hypotrophic) of the cross-sectional area.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular smooth muscle cell structural changes in cardiovascular diseases and aging are collectively termed vascular remodeling [40]. Vascular remodeling is observed when there is a change in diameter of a fully relaxed vessel that is not explained by a change in transmural pressure or compliance, and thus is structural in nature [40]. Remodeling can be increase (hypertrophic), no change (eutrophic) or decrease (hypotrophic) of the cross-sectional area.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease is the leading cause of death in the general population [28]. Hypertension induces morphological and physiological changes in the arterial wall [29]; therefore, the regression of these changes is one of the goals of antihypertensive therapy [7] in order to reduce the incidence of adverse cardiovascular events [5,6]. Several studies have shown changes in aortic remodeling (a reduction in aortic wall thickness) in SHRs as a result of antiarrhythmic and antihypertensive therapy (β-adrenergic blockers, ACE inhibitors, angiotensin receptor antagonists, and calcium channel blockers) [19,3034].…”
Section: Discussionmentioning
confidence: 99%
“…The deleterious effects of hypertension include arterial remodeling (increased wall thickness) [29], and a single-vessel occlusion can significantly reduce the blood flow in ischemia [46]. Hypertension is the leading cause of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Acting as critical rheostats, CSK machinery is dynamic allowing cells to adapt to mechanical perturbations in the microenvironment 6 . Evidence suggests that abnormal acclimation of VSMC to biomechanical perturbations, such as increased circumferential stress in hypertension can impact VSMC signaling and stimulate AAA development [7][8][9] . However, insights into the change of VSMC CSK integrity and the resulting pathological mechanosensation in AAA have not been explored.…”
Section: Introductionmentioning
confidence: 99%